2020
DOI: 10.17796/1053-4625-44.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of a Resin Composite to Six Pulp Capping Materials Used in Primary Teeth

Abstract: Aim: The purpose of this in vitro study was to assess the shear bond strength (SBS) and bond failure types of a resin-composite to six pulp-capping materials used in primary teeth. Study design: Eight-disc specimens from each pulp-capping material (6 groups) to bond to Filtek™ Z350 XT Flowable using a standard PVC tube (2×2mm). All groups were prepared according to the instruction of the manufacturer. The SBS was measured with a crosshead speed of 0.5 mm/min using a universal testing machine. Failure mode eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…In this study, the mean SBS of ProRoot MTA with delayed RC placement was comparable to the previous investigations [30][31][32]34,35]. However, it was lower than in Alhowaish et al, where they reported the SBS of ProRoot MTA to be 22.11 MPa; this high value could be due to the different methodology used in their study, where they used cylindrical metal molds to fabricate disc specimens as well as 35% phosphoric acid etching and the application of two consecutive coats of the adhesive system [33]. In this study the mean SBS of NeoMTA2 with delayed RC placement was comparable with the mean SBS of NeoMTA to delayed RC in Hursh et al's study (5.72 MPa) [34].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, the mean SBS of ProRoot MTA with delayed RC placement was comparable to the previous investigations [30][31][32]34,35]. However, it was lower than in Alhowaish et al, where they reported the SBS of ProRoot MTA to be 22.11 MPa; this high value could be due to the different methodology used in their study, where they used cylindrical metal molds to fabricate disc specimens as well as 35% phosphoric acid etching and the application of two consecutive coats of the adhesive system [33]. In this study the mean SBS of NeoMTA2 with delayed RC placement was comparable with the mean SBS of NeoMTA to delayed RC in Hursh et al's study (5.72 MPa) [34].…”
Section: Discussionsupporting
confidence: 78%
“…A variety of restorative materials are used in VPT including zinc oxide-eugenol cement base (ZOE), IRM, resin-modified glass ionomer (RMGI), and resin composite (RC) [25][26][27][28]. The shear bond strength (SBS) between MTA and RC has been evaluated in multiple studies using different etching and bonding techniques, which resulted in a wide range of values [29][30][31][32][33][34][35][36][37][38]. The SBS of RC to premixed bioceramics has been investigated in limited studies and reported to be lower than MTA [34,39].…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, 5017 studies were excluded after reviewing the titles and abstracts, leaving 41 articles to be assessed by full-text interpretation. After the full-text assessment, four studies were excluded, three because the access to the full document was not achieved [17][18][19], and one because the manuscript was in a language different than English [20]. A total of thirty-seven manuscripts were included in the qualitative analysis, and from these, fifteen were excluded from the meta-analysis because they did not compare a self-etch adhesive against a total-etch adhesive [10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…The various models used are extracted permanent premolar 29,30 or molar teeth, 17,31 artificial models like acrylic resin blocks 32,33,34,35 and disk specimens. 36,37 The total sample size ranges between 20-600 teeth or model. Out of ten studies, seven articles included Biodentine, five included TheraCal LC and three included Similarly, five studies used Universal adhesive, 17,29,30,31,37 five used Adper Single bond 3M ESPE 32,33,34,35,36 as adhesives with a curing time ranging from 10-20 seconds.…”
Section: Descriptive Analysismentioning
confidence: 99%